ANALISIS DAYA DUKUNG LAHAN PERTANIAN TANAMAN PANGAN TERHADAP KESEJAHTERAAN EKONOMI RUMAH TANGGA PETANI DI KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Rizqia Ayu Sucita; Candra Ayu; Abdullah Usman (JURNAL AGRIMANSION, 2023)
The area of farmers land in Praya District has decreased by 9 ha or 0.0027% in 2021. This means that the carrying capacity of agricultural land will be smaller. Prior to land conversion, most of the land belonged to farmers used to grow food crops. This study aims to (1) analyze the carrying capacity of agricultural land for food crops in Praya District; (2) Analyze the income of food crop farming and its contribution to the household income of farmers in Praya District; (3) Analyze the level of economic welfare of food crop farmer households in Praya District; and (4) Knowing the problems and obstacles faced by farmers in carrying out food crop farming in Praya District. The method used in this research is descriptive method. The research area was determined by purposive sampling. Determination of the number of respondents was determined using the slovin method as many as 42 respondents. The results of the analysis show that (1) The CCR value of food crop farming in Praya District to the number of farmer family members is 2,98. (2) The average income of rice farming in MT I was IDR Rp13.954.756,85/ha, rice farming income in MT II was IDR Rp12.132.750,54/ha, corn, green bean, and soybean farming income in MT III amounted to IDR 13.792.449,43/ha, this income contributed 31,28% to farmer household income. (3) The average income of farmers from farming activities, farming outside of their own farming, from outside of farming, and other sources is still classified as not prosperous. (4) The problems and obstacles faced by farmers are: low productivity, pest attack, and marketing